If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -2) + 11x + -5 = 0 Reorder the terms: 4(-2 + 5x) + 11x + -5 = 0 (-2 * 4 + 5x * 4) + 11x + -5 = 0 (-8 + 20x) + 11x + -5 = 0 Reorder the terms: -8 + -5 + 20x + 11x = 0 Combine like terms: -8 + -5 = -13 -13 + 20x + 11x = 0 Combine like terms: 20x + 11x = 31x -13 + 31x = 0 Solving -13 + 31x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 31x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 31x = 0 + 13 31x = 0 + 13 Combine like terms: 0 + 13 = 13 31x = 13 Divide each side by '31'. x = 0.4193548387 Simplifying x = 0.4193548387
| 13-x=45 | | x+100=x+36 | | x(2x+7)=114 | | 2x+79+7x=14 | | -9+5+4=x+23 | | 2=14-2z | | 9v-v=16 | | (2X+3)-(7x+5)= | | log(9x+8)=2+log(4x-5) | | 1x+(-21)=-31 | | x+8=x+26 | | 6u+u=7 | | 3-4(u-3)=5-u | | 4x-9y=19fory | | 12=6y-2y | | 5a+3-9a+6= | | 7x+3-4=7x+2-3 | | -9p=-36 | | 3m+-5+2m=7m+-24+5 | | v/2=1.77 | | 4y+9=19 | | (2n-2)=(8n+1) | | -30-x=0 | | 4x+3=11x+17 | | 2(v-6)-(-3+6v)=1-2v-2v | | u=3(4n+34)+7(n+1) | | -15x=-90 | | 2y+35=9y-7 | | n=3+3 | | 2x+42=x+42 | | 2(v-6)-(-3+6)=1-2v-2v | | 2s-10=s-2 |